FAKTOR – FAKTOR YANG MEMPENGARUHI CURAHAN JAM KERJA TENAGA SEKTOR INFORMAL DI KOTA PEKANBARU - Dewi, Rahmi; Maulida, Yusni; Widayatsari, Any (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The informal sector is believed to be able to sustain the economy in Riau Province, this can be shown by data from BPS which mentions 52.70 percent of Riau's work force in the informal sector. This study aims to analyze the factors of wages, education, age and the number of family dependents on the outpouring of working hours of informal sector workers in Pekanbaru City.This research was conducted in Pekan Pekan Baru, with sample of 90 respondents with total population 147,119 people. Determination of sample by snow ball samlpling method. Data analysis method used in this research is doubled linear regression or OLS with work hour as dependent variable and four independent variable that is wage, education, age and amount of family dependent. Data collection techniques used interview method assisted by questionnaire. The result of the analysis shows that the variable of wage, education, age and the number of family dependents have no significant effect on the outpouring of working hours of informal sector workers in Pekanbaru City.Keywords : Working Hours, Wages, Education, Age, Total Family Count, Informal Sector